"The Course of Love Never Did Run Smooth": Ex-Inmates' Attitudes Toward Heterosexual Romantic Relationships. (June 2022) - Granot, Noa; Einat, Tomer
This study examines the attitudes of 15 male ex-inmates toward heterosexual romantic relationships during imprisonment as viewed retrospectively. The interviewees expressed ambivalence regarding these intimate partnerships, which were a source of difficulty in prison and upon reentry into society. We conclude that prison services could better help inmates to improve these relationships, thus reducing the pains of imprisonment and enhancing their successful social reintegration.